Integrated and Sequential Enzyme-Assisted Extraction of Fucoidan and Alginate from Sargassum echinocarpum - Sugiono, Sugiono; Hidayat, Mohammad Taufiq; Wahyuni, Endang Tri; Syafii, Syafii; Fikriyatullatifah, Anisa; Mumtazah, Lutfia Anis (The Journal of Experimental Life Science, 2025)
The sequential extraction biorefinery process can use brown algae as its feedstock, offering a sustainable approach to maximizing the utilization of marine biomass for high-value bioactive compounds. This method enables the recovery of multiple bioactive components from a single raw material, increasing process efficiency and reducing waste. Fucoidan and alginate, two valuable polysaccharides in brown algae, have attracted significant attention due to their diverse applications in the pharmaceutical, nutraceutical, and food industries. This research aims to develop an enzyme-assisted extraction (EAE) process that maximizes the fucoidan yield of Sargassum echinocharpum in the integrated alginate and fucoidan extraction biorefinery process. The effect of the parameter process, including temperature, time, and solvent-to-algae ratio, was evaluated to maximize fucoidan and alginate yield and determine the correct equation model in the first order of the experiment. The study showed that temperature, time, and the ratio of solvents all had a real effect on how quickly the fucoidan and alginate yields increased and then decreased after reaching their highest point. The temperature of 50°C, time of 24 hours, and the solvent-to-algae ratio of 30:1 (v/w) resulted in the highest fucoidan yield of 4.25% and alginate yield of 35.3%,  along with an intrinsic viscosity of 78.91 mL.g-1, molecular weight of 73.58 kDa, and an M/G ratio of 0.35.  Statistical analysis revealed a quadratic relationship, suggesting the presence of an optimal extraction condition. These findings highlight the potential of enzyme-assisted biorefinery techniques for improving fucoidan and alginate extraction. This extraction process demonstrates significant potential for industrial-scale application in the food, pharmaceutical, and nutraceutical industries due to its efficiency and sustainability.